2005
DOI: 10.1021/ma047955c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bis(2,2‘:6‘,2‘ ‘-terpyridine)ruthenium(II)-Connected Diblock Polymers via RAFT Polymerization

Abstract: We report the synthesis and uses of a novel terpyridine-functionalized chain transfer agent (CTA) that produces well-controlled macromolecular architectures with terpyridine functionalities at one chain end via reversible addition-fragmentation chain transfer (RAFT) polymerization. The terpyridineterminated macromolecules with well-defined structures were further used for preparation of supramolecular diblock metallomacromolecules by bis(2,2′:6′,2′′-terpyridine)ruthenium(II) complex connectivity. The successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 79 publications
2
61
0
Order By: Relevance
“…Bipyridine (101; Scheme 12) [193] and terpyridine (102) functional dithioesters [194] have been used in RAFT polymerization and thence to form ruthenium complexes. The RAFTsynthesized polymer formed with 102 was used to make ruthenium connected polystyrene-(Ru II )-PNIPAM blocks.…”
Section: S Smentioning
confidence: 99%
“…Bipyridine (101; Scheme 12) [193] and terpyridine (102) functional dithioesters [194] have been used in RAFT polymerization and thence to form ruthenium complexes. The RAFTsynthesized polymer formed with 102 was used to make ruthenium connected polystyrene-(Ru II )-PNIPAM blocks.…”
Section: S Smentioning
confidence: 99%
“…[30] Many [199,223] NIPAm [199,223] NIPAm [279] -CH 2 CN VAc [67] -CH 2 CO 2 H MMA [115] Sty [115,144,215] AA [248] VAc b) [144] b) [144] StySO 3 Na [235] BA [115] a) [215] StyOCOMe [240] DMAm [286] NAM [43,286] -CH 2 CO 2 Me VAc [313,328,329,333] b) [330] -CH 2 CO 2 Et MMA [115] Sty [115] BA [115] -CH 2 CO 2 CH 2 CH 2 C 6 F 13 MMA [113] Sty [113] B [113] -CH 2 CON(Me) 2 DMAm [285] -CH 2 CH 2 Ph VAc [327] VPr [327] -CH 2 CH 2 C 8 F 17 MMA [113] Sty [113] Sty [338,339] BA [338] -H MMA [116] Sty [116,192] MA [116,192] -SC(Me) 3 MMA …”
Section: Influence Of Experimental Conditionsmentioning
confidence: 99%
“…Sugiyama [14b] found that no peak appeared for the expected polymer at all in the GPC curves of AB diblock copolymers or AB 2 star copolymers linked by ionic bonding; while Zhou and Harruna reported that there was no RI signal corresponding to the metallo-coordination block polymers. [19] Moreover, Ghiggino et al [20] noticed that the molecular weights of metallo-supramolecular star polymers detected by GPC [M n ðGPCÞ] were much lower than those calculated by other methods (theoretic or calculated by the UV/vis method). Because of this, here it is important that the molecular weight of the supramolecular star polymers was determined by 1 H NMR measurements.…”
Section: Synthesis Of Supramolecular Star Homopolymersmentioning
confidence: 99%